God's pattern for Creation a covenantal reading of Genesis 1 - Godfrey, W. Robert (Phillipsburg, NJ Presbyterian and Reformed, 2003)
Includes bibliographical references.
Keywords: Creationism -- history of doctrines; Bible. O.T. Genesis I -- criticism, interpretation, etc